Natural Products as Potential Inhibitors for SARS-CoV-2 Papain-Like Protease: An in Silico Study - Alvarado-Huayhuaz, Jesus; Jimenez, Fabian; Cordova-Serrano, Gerson; Camps, Ihosvany; Puma-Zamora, Wilmar (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
In December 2019 in Wuhan, China, the first case of a patient infected with a new coronavirus was reported, later called SARS-CoV2 by the World Health Organization, and so far, there is no approved drug or vaccine against this new virus. Considering this, previous studies identified several essential SARS-CoV-2 viral proteins, among these to the papain-like protease (PLpro), an enzyme with an important role in viral spread and evading the host immune response, making it an attractive drug target. For this reason, using a library of 213,038 structures of natural products and virtual screening, we identified 10 molecules with high aﬃnity for residues of the SARS-CoV-2 PLpro allosteric site, which could be tested in vitro against the virus or as lead-compounds to develop inhibitors that are more eﬀective.